(untitled) (Journal of Science Foundation, 2019)
Background: Maternal outcome is an important issue among the primigravida women presented with fetal head engagement. Objectives: The purpose of the present study was to observe the maternal outcome of among the primigravida women presented with fetal head engagement. Methodology: This descriptive cohort study was carried out in the Department of Gynecology and Obstetrics at Sir Salimullah Medical College and Mitford Hospital, Dhaka from June 2006 to December 2006 for a period of sic (6) months. Primaigravida women with 38 or more weeks of pregnancy having single foetus with cephalic presentation were selected as study population. Maternal outcome was measured in terms of incidence of post-partum hemorrhage, injury to the birth canal, wound infection and puerperal sepsis. Result: A total number of 1440 pregnant women were recruited for this study. Maximum number of patients was in the age group of 21 to 24 years which was 897(62.29%). Post partum hemorrhage (PPH) was reported in 7(2.67%) cases in engaged group and 17(1.44%) cases in non-engaged group. Birth canal injury was recorded in 4(1.53%) cases and 12(1.02%) cases in engaged and non-engaged group respectively. Wound infection was found in 8(3.05%) cases and 81(6.88%) cases in engaged and non-engaged group respectively. Regarding puerperal sepsis it was found in 3(1.15%) cases and 11(0.93%) cases in engaged and non-engaged group respectively Conclusion: In conclusion PPH, birth canal injury, wound infection and puerperal sepsis are commonly found in non-engaged group Journal of Science Foundation 2018;16(2):34-37